FROM HOME TO PUBLIC SPACE: The Role Of Women In The Qur'anic Perspective - Khodijah, Dedek Nursiti; Alif Utama, Mohamad Maulidin; Nurrochim, Zuni; Santi, Nani Endri; Nurhanifah, Nurhanifah; Milia Islamia, Alvi Jamia (STAI Asy-Syukriyyah, 2024)
Feminism among Muslims has become a topic of interest due to globalization. The value of gender equality is upheld in Islam, emphasizing women's rights and egalitarianism. Women play an important role in society, both in social, economic and political contexts. In Islam, the Koran provides comprehensive guidance regarding the rights and obligations of women. A deep understanding of the verses of the Koran regarding women is very important to respond to the challenges they face in the public sphere. The aim of this research is to analyze the role of women from various sectors from the perspective of the Qur'an. This research method is a literature review which collects data and analyzes data from library sources related to the role of women in the Qur'an. The results of this research are that there are differences of opinion, the Koran allows women to participate in public spaces, with certain conditions. However, women's main role as mothers and wives should not be ignored, because this is their intrinsic nature.